Die frühmittelhochdeutsche fragmentarische Übersetzung des pseudo-galenischen De dynamidiis - Valeria Di Clemente (Filologia Germanica)
THE EARLY MIDDLE HIGH GERMAN FRAGMENTARY TRANSLATION OF THE PSEUDOGALENIC ‘DE DYNAMIDIIS’. The so-called Bamberger Arzneibuch (c. 1150) is the earliest medical book preserved in German language. It contains three fragmentary texts: the Arzenībuoch Ypocratis, a collection of medical remedies attributed to Hippocrates, a great part of which is also recorded in medieval Latin medical literature; a translation of the oldest Latin version of a lateantique prognostic work, also attributed to Hippocrates; a translation of De dynamidiis, a small fragmentary Latin text attributed to Galen, where names and qualities of some medicines are explained. In this paper an updated critical reading of De dynamidiis is proposed, jointly with an analysis of some particularly interesting terms used in the German translation. The fragment seemingly undergoes a function change through the translation process, becoming a sort of bilingual glossary where the definitions, which are translated into German, help the reader/learner understand the meaning of the Greek-Latin technical terms.